Penerapan Pembelajaran Kontekstual Dalam Meningkatkan Keterampilan Menulis Narasi Pada Siswa Sekolah Dasar - Fatimah Rahmi Hidayati; Melva Zainil (GLOBAL SCIENTS PUBLISHER, 2025)
The teaching of Indonesian language in elementary schools plays a crucial role in developing students' literacy skills, particularly in narrative writing. However, in practice, many students struggle with generating ideas, constructing storylines, and utilizing proper language structures. This study aims to assess the effectiveness of the Contextual Teaching and Learning (CTL) approach in enhancing narrative writing skills among fifth-grade elementary students. A quasi-experimental design with a pretest-posttest control group approach was employed. The study involved two groups: the experimental group received instruction based on CTL, while the control group was taught using conventional methods. Data analysis indicated a significant improvement in the narrative writing skills of students in the experimental group compared to the control group. The CTL approach was shown to be effective in improving students' learning outcomes by relating lesson content to real-life experiences, while also fostering active participation and creativity. These findings suggest that CTL can be an effective instructional strategy for teaching writing in elementary schools.